Deterministic local multi-point fault detection method for industrial control topology - Ruozhou LIANG; Xibin ZHAO; Hai WAN (Tongxin xuebao)
In view of the fact that the existing network fault detection algorithms cannot meet the four requirements of determination of detection time, low detection overhead, multi-point fault detection ability and topology adaptability of industrial control network at the same time, a multi-point fault detection method of time sensitive network based on Boolean network mapping was proposed.The method was divided into offline preparation phase and online detection phase.In the offline preparation phase, the detection flow generation algorithm generated a set of detection flows based on the network topology.The detection flow set covered the edges of the network topology.In the online detection phase, the detection packet was sent periodically from the source node to the controller according to the predefined path.Then, the controller inferred the failed link according to the arrival state of each detection packet.The experimental results show that, compared with the existing methods, the proposed method can accurately identify multiple failed links in a certain time, and generate fewer detection path sets to meet the above four requirements.